The Effect of Job Stress and Reward System on Organizational Commitment and Employee Performance - Adhisty Merrial Oya (International Journal of Review Management Business and Entrepreneurship (RMBE), 2021)
The purpose of this study was to investigate the relationship between job stress and reward systems on organizational commitment and employee performance. The subjects in this study were employees in manager level, namely IPOMS (Indonesian Production and Operation Management Society) with 119 respondents. The data collection method is done by distributing questionnaires using an interval scale of 1 to 7 and using data analysis methods Structural Equation Modelling (SEM) – Partial Least Square (PLS). The result showed that there is no significant relationship between work stress and organizational commitment, there is a significant relationship and positive between reward system and organizational commitment, there is no significant relationship between work stress and employee performance, there is no significant relationship between reward system and organizational commitment, there is a significant relationship and positive between organizational commitment and employee performance.